Midwives’ practice and perception of labour and delivery care at the Mulago National Referral Hospital, Uganda - Namwaya, Ziidah; Namagembe, Imelda; Kaye, Dan; Nalwadda, Gorrette; Edwards, Grace; Nabirye, Rose Chalo (African Journal of Midwifery and Women's Health, 2020)
The majority of maternal deaths occur during labour, delivery, or within the first 4 hours after birth. This can be reduced by the care that midwives provide. At Mulago Hospital, little is documented on midwives' current practice and their perception of care offered during labor and delivery. The number of maternal and neonatal deaths as a result of preventable causes such as postpartum haemorrhage, obstructed labour, ruptured uterus and sepsis remains high. The aim of this study was to document the current practice of midwives, explore midwives' perception towards practice and identify factors that influence practice during birth in Uganda, to identify possible areas for improvement. A cross-sectional study was conducted of midwives working in the three labour wards at the Mulago National referral hospital: the general ward, the private ward and the midwifery-led ward. Midwives' perceptions were explored using a semi-structured questionnaire, which asked midwives about their current practice and their perception of the care offered. Care was found to be lacking in several areas. Only one-fifth (20.0%) of midwives reported always checking temperature every 4 hours. Only 20.5% reported that women are always supported in being mobile during labour. Less than half of the midwives (44.4%) knew the recommended drugs for managing the third stage of labour. Infection prevention practices were poor. Only 54% of midwives knew how to prepare magnesium sulphate for management of severe pre-eclampsia and eclampsia. Overall, the general labour ward was found to have the most gaps in midwives' knowledge. Lack of continuing education, supplies, teamwork and clinical guidelines were reported to affect practice. Staff shortages and midwives' decisions being underlooked by obstetricians were also reported to affect practice. Overall, the study found that midwifery practice is suboptimal in key areas such as infection prevention, use of a partograph, and management of pre-eclampsia and eclampsia. Continuous professional development, provision of resources, and strengthening teamwork are recommended to improve maternal health outcomes at Mulago Hospital.